SILVERING ASPECTS AND IMPACT OF ANGUILLICOLA CRASSUS ON EUROPEAN EELS FISHED IN THE MAFRAGH ESTUARY (WESTERN MEDITERRANEAN) - DIA, SALOUA; DJEBBARI, NAOUELE; TAHRI, MARDJA; GOUTAL, YASSA; ABDALAH, WISSAL KHADIJA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
In this study, we focused our research on the impact of the nematode Anguillicola crassus on the growth and silvering mechanism of the structural eel subpopulation in the Mafragh Estuary using a rapid method that allowed us to identify silver eels that migrate to the Sargasso Sea the following season. The results of our study show that the fraction of the eel population present, a mean length, as 634.52 ± 73.84 mm, a mean weight as 532.43 ± 225.31 g and the mean age was 4.45 ± 1.09 years. The sex ratio observed is in favor of silver females (70%). In the latter, the average OI value exceeds 11% and that of FI is above 5%. The highest mean GSI values were found in migrating females of stage IV (0.93%±0.34) and stage V (0.94%±0.54); Migrant eels of stage IV show the lowest mean HSI values (1.29%±0.27) and IGu values (1.66±0.87) and the highest Mean K-value (0.248± 0.068) despite their high infestation with A. crassus (P = 66%, I=11.5 worms/infested eel; A = 7.67 worms/examined eel).